Growth Strategy for Start-Up Businesses: Analysis of Solutions for Scalability, Marketing, and Risk Management - Yuwono, Imam; Rakhmawati, Nur Endah; Putri, Nurulita Purnama (Jurnal Ilmiah Manajemen dan Bisnis, 2024)
Start up businesses experiencing difficulties in their growth process, especially in terms of scalability, marketing, and risk management. Scalability is the ability of a business to increase its operational scale without reducing efficiency and effectiveness. Marketing is the process of promoting a product or service so that it is known to the public and attracts consumer interest. Risk management is an action taken by the company to reduce the negative impact of unwanted events. Based on this background, research will be carried out entitled: "Business Start-up Growth Strategy: Analysis of Solutions for Scalability, Marketing and Risk Management”. The methods used in this study are qualitative and quantitative research methods. Qualitative research methods are used to gain an in-depth understanding of solutions for scalability, marketing, and risk management Start up business. In this case the researcher will conduct an interview with the founder or manager of the Start up, view and analyze related documents and records, and make direct observations. on activities Start up. The purpose of this research is to analyze how this happens. Start-up businesses can overcome difficulties such as scalability, marketing, and risk management as they grow and provide recommendations for effective growth strategies can overcome problems and can help strengthen the business sector and make a positive contribution to the economy. To provide enlightenment to the public, the results of the research will be published in an Accredited Journal.